Incentivos y desincentivos para la participación del Perú en el sistema multilateral del tratado internacional sobre recursos fitogenéticos para la alimentación y la agricultura - Lapeña, I.; López, I.; Sigueñas, M.; Ramírez, M. (2010)
Contains a recently conducted study on incentives and disincentives for the participation of Peru in the Multilateral System of the Treaty, describes the demand, exchange and use of plant genetic resources in Peru. The study also identifies opportunities for Peru resulting from the exchange of these genetic resources with other countries in the Multilateral System. Ten aspects of the Treaty are analyzed in the study, from the level of awareness and understanding of what the Treaty is, to the favorable and unfavorable conditions affecting its implementation in Peru. The study was conducted through a World Bank-funded project titled Collective Action for the Rehabilitation of Global Public Goods, which was implemented through the CGIAR System-wide Genetic Resources Programme–SGRP